Diagnosis and treatment of a patient with isolated spinal granulocytic sarcoma: A case report - XIAO, RUO-ZHI (D.A. Spandidos, 2013)
A previously healthy 34-year-old female presented with a 5-month history of progressive backache and weakness in the left fingers. Magnetic resonance imaging (MRI) showed soft tissue masses in the spinal canal distributed along the nerve course. The patient’s baseline laboratory data were normal. Surgical intervention was performed and histological examination identified isolated spinal granulocytic sarcoma (GS). A bone marrow biopsy also presented normal findings. However, the patient developed numbness and pain in the right lower limb two months later. Fluorodeoxyglucose (FDG)-positron emission tomography (PET) showed FDG uptake in the left trapezius muscle, cervix uteri, iliac bone, lymphadenectasis of the pelvic wall and left axillary fossa. Cerebrospinal fluid (CSF) examination allowed a diagnosis of central nervous system leukemia (CNSL). The patient underwent chemotherapy and intrathecal injection, resulting in the elimination of the residual lesion. Correct diagnosis and adequate treatment are essential to achieve optimal results in patients with isolated spinal GS.